ESKETAMINE AND DEEP BRAIN STIMULATION IN TREATMENT-RESISTANT DEPRESSION: A LITERATURE REVIEW - Jolanta Wiśniewska; Mikołaj Wiśniewski; Weronika Buczek; Piotr Bartnik; Karolina Barzyk; Magdalena Pietrzak (International Journal of Innovative Technologies in Social Science, 2026)
Background: Depression is a significant mental health condition affecting numerous individuals worldwide, leading to disability within society and posing a heightened risk of suicide, thereby diminishing overall quality of life. Depression, often a contributing factor in suicides, is associated with various prevalent medical conditions such as obesity, diabetes, stroke, Parkinson’s disease, and multiple sclerosis. Treatment-resistant depression (TRD) affects approximately 30% of patients with major depressive disorder. Aim of the study: This study aims to assess the efficacy of modern depression treatments such as intranasal esketamine administration and deep brain stimulation. Material and methods: A review of literature was conducted using several scientific databases, including PubMed, Scopus, Web of Science, and Google Scholar. Only articles in English were included for further analysis. The keywords used were: “depression”, “esketamine”, “ketamine”, and “deep brain stimulation”. Ultimately, 30 articles were selected for analysis. Results: Intranasal esketamine has shown promising results, including improved well-being and alleviation of symptoms, although caution is advised in patients with hypertension. While deep brain stimulation is traditionally used for movement disorders like Parkinson’s disease, recent findings suggest its potential as a viable treatment for severe depression. Long-term studies indicate that both approaches effectively facilitate remission of depression. Conclusions: Depression poses a significant threat to individuals’ health and well-being, necessitating a comprehensive treatment approach. Tailored strategies encompassing pharmaceutical interventions, surgical procedures, and psychotherapy can collectively contribute to substantial improvements in daily functioning and reduce the risk of suicidal behaviors.